Binding Immunoglobulin Protein (BIP) Inhibits TNF‐α–Induced Osteoclast Differentiation and Systemic Bone Loss in an Erosive Arthritis Model. Issue 6 (3rd August 2019) - Zaiss, Mario M.; Hall, Christopher; McGowan, Neil W. A.; Babb, Rebecca; Devlia, Vikesh; Lucas, Sébastien; Meghji, Sajeda; Henderson, Brian; Bozec, Aline; Schett, Georg; David, Jean‐Pierre; Panayi, Gabriel S.; et al.
Abstract : Objective: The association between inflammation and dysregulated bone remodeling is apparent in rheumatoid arthritis and is recapitulated in the human tumor necrosis factor transgenic ( hTNF tg) mouse model. We investigated whether extracellular binding immunoglobulin protein (BiP) would protect the hTNF tg mouse from both inflammatory arthritis as well as extensive systemic bone loss and whether BiP had direct antiosteoclast properties in vitro. Methods: hTNF tg mice received a single intraperitoneal administration of BiP at onset of arthritis. Clinical disease parameters were measured weekly. Bone analysis was performed by microcomputed tomography and histomorphometry. Mouse bone marrow macrophage and human peripheral blood monocyte precursors were used to study the direct effect of BiP on osteoclast differentiation and function in vitro. Monocyte and osteoclast signaling was analyzed by Western blotting, flow cytometry, and imaging flow cytometry. Results: BiP‐treated mice showed reduced inflammation and cartilage destruction, and histomorphometric analysis revealed a decrease in osteoclast number with protection from systemic bone loss. Abrogation of osteoclast function was also observed in an ex vivo murine calvarial model. BiP inhibited differentiation of osteoclast precursors and prevented bone resorption by mature osteoclasts in vitro. BiP also induced downregulation of CD115/c‐Fms and Receptor Activator of NF‐κB (RANK) messenger RNA and protein, causing reduced phosphorylation of the p38 mitogen–activated protein kinases, extracellular signal–regulated kinases 1/2 and p38, with suppression of essential osteoclast transcription factors, c‐Fos and NFATc1. BiP directly inhibited TNF‐α– or Receptor Activator of NF–κB Ligand (RANKL)–induced NF‐κB nuclear translocation in THP‐1 monocytic cells and preosteoclasts by the canonical and noncanonical pathways. Conclusion: BiP combines an anti‐inflammatory function with antiosteoclast activity, which establishes it as a potential novel therapeutic for inflammatory disorders associated with bone loss.